The role of assay methods in characterizing the quality of bulk pharmaceuticals - Wieslawa Misiuk (Wolters Kluwer Medknow Publications, 2010)
This study presents the role of assay methods in characterizing the quality of bulk substances in pharmaceutical analysis. High-performance liquid chromatography (HPLC) is the most remarkable development and the technique has become very significant in the quality control of bulk drugs and pharmaceutical formulations, even at the pharmacopoeial level. Development of HPLC and other chtromatographic techniques, coupled with mass spectrometry, is also useful in the determination of drugs and their metabolites in biological samples. The role of electrophoretic, spectroscopic, and other methods in pharmaceutical analysis are discussed here. There are separate sections devoted to microscopy techniques that are useful in the pharmaceutical field, as also the regulatory aspects of drug analysis, with emphasis on questions related to validation.